On the Wicksellian Point-Input, Point-Output Model of Capital Accumulation: A Modern View (or, Neoclassicism Slightly Vindicated) - Cass, David (Journal of Political Economy, 1973)
This is primarily an expository paper, presenting many of the concepts and results of modern capital theory in the context of analyzing Wicksell's classical model of natural aging processes. The only novel result is a demonstration that efficient allocation over time in the Wicksellian model implies that real (though not value) aggregation can be utilized to reduce it, for all practical purposes, to the well-known one-sector neoclassical model.